1978
DOI: 10.1002/1097-4679(197810)34:4<857::aid-jclp2270340407>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Logical and nonlogical classification systems: A look at the underlying complexity of overinclusion in schizophrenics

Abstract: Although overinclusion is hypothesized to be a thought disorder, it has been found to be related to positive variables – good prognosis, good premorbidity, and good picture recognition. We hypothesized that some overinclusive responses involved an alternative classification system to conventional logical classification and that these alternative systems might facilitate picture recognition performance. Twenty‐seven male schizophrenics were given the Object Classification Test, the Object Sorting Test, and a pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
2

Year Published

1978
1978
2004
2004

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
0
5
2
Order By: Relevance
“…Numerous researchers have investigated the teacher retention problem in agricultural education (Bryant, 1980;Cole, 1984;Dillon, 1978;Edwards & Briers, 2001;Flowers & Pepple, 1988;Grady, 1988;Howell & Martin, 1983;Knight, 1978;Moore & Camp, 1979;Reilly & Welton, 1980). Although the problem has been investigated in prior research, a review of the literature indicates that a majority of the studies which identified the reasons why agriculture teachers left the profession were published prior to the 1990s.…”
Section: Introduction/theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous researchers have investigated the teacher retention problem in agricultural education (Bryant, 1980;Cole, 1984;Dillon, 1978;Edwards & Briers, 2001;Flowers & Pepple, 1988;Grady, 1988;Howell & Martin, 1983;Knight, 1978;Moore & Camp, 1979;Reilly & Welton, 1980). Although the problem has been investigated in prior research, a review of the literature indicates that a majority of the studies which identified the reasons why agriculture teachers left the profession were published prior to the 1990s.…”
Section: Introduction/theoretical Frameworkmentioning
confidence: 99%
“…The issue of secondary teacher job satisfaction and retention has been the focus of research across disciplinary boundaries for several years (Chapman, 1983;Chapman, 1984;Chapman & Green, 1986, Cole, 1984Knight, 1978;McBride, Munday & Tunnell, 1992;Miller 1974;and Reilly & Welton, 1980). These studies have identified personal characteristics, student concerns, workload, recognition received, salary, and policyadministration as common turnover and job dissatisfaction factors.…”
Section: Introduction/theoretical Frameworkmentioning
confidence: 99%
“…Overinclusive thinking long has been considered a central feature of schizophrenic thought disorder (Cameron, 1944) and has been the subject of extensive investigation (Chapman & Chapman, 1973). Although this area has been plagued by numerous difficulties, including low correlations between the various measures used to assess overinclusion (Watson, 1967) and failures to replicate past findings (Payne, Hochberg, & Hawks, 1970), interest in the nature of overinclusive thinking remains strong (Craig & Verinis, 1979;Sims-Knight & Knight, 1978).…”
Section: State University Of New York At Bujtalomentioning
confidence: 99%
“…Overinclusion also has bccn rclatcd to efficient information proccssing on tasks that reflect iconic mcmory (Knight, Sherer, & Shapiro, 1977) and recognition memory for verbal (Bauman & Murray,196s) and pictorial stimuli (Knight, Sims-Knight, & Petchers-Cassell, 1977). Recent authors have recognized the possiblc significancc of these findings for understanding thc nature of overinclusive thinking in schizophrcnia (Chapman & Chapman, 1973;Sims-Knight & Knight, 1978). I n a recent study, Knight, Sims-Icnight, and Petchers-Cassell (1977) proposcd that overinclusion may reflect the ability to scan stimuli broadly; that is, to process a large numbcr of attributes of a stimulus array.…”
Section: State University Of New York At Bujtalomentioning
confidence: 99%
See 1 more Smart Citation